Upaya Peningkatan Kesehatan Gigi dan Mulut Melalui Pendidikan dan Pelatihan “SENI SEHAT” - Yutanti, Wulan Tri; Setiyono, Andik (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
Dental and oral health problems, such as dental caries in school-age children, are a challenge for public health. The “SENI SEHAT” (Sejak Dini Menjaga Agar Gigi Sehat dan Kuat) program intervention can be provided as a preventive measure. The program implementation method used was a one-group pretest-posttest design to assess the effect of the intervention offered through lectures, question-and-answer sessions, and toothbrushing practice. Based on the Wilcoxon statistical test, a significant difference was found between the level of knowledge before (pretest) and after (posttest) the intervention was administered (p-value < 0.05). Through the “SENI SEHAT” program, it has been proven effective in increasing oral health knowledge among elementary school children. The educational and training approach in this activity can contribute to reducing the burden of dental and oral health problems, especially those related to dental caries, by emphasizing the importance of providing health education on maintaining dental and oral health, proper toothbrushing practices, and comprehensive dental and oral health education to create a healthier population.